Study of the variability of physicochemical parameters in different fractions of corn and espartillo intended for the production of solid biofuels - Bernard, Mariana del Valle; Belmonte, Luciana Micaela; Quicchi, Agostina Lucía; Farías, Adela (DYNA, 2026)
The current context of the energy transition is driving the development of alternative fuels, such as lignocellulosic materials of agricultural origin. This study analyzed the variation in physicochemical parameters in fractions of espartillo (E) and corn stover (RM) according to particle size. It was observed that reducing the particle size in RM increased the ash and extractive content, while E only showed an increase in ash. Pure materials and hybrid mixtures of E/RM 1:1 and 1:3 were evaluated in combustion. The 1:1 mixture reached a higher combustion temperature, exhibited a longer flame duration, and had an optimized heating value, although it had a higher ash content that could be reduced by removing particles smaller than 149 μm. The results obtained demonstrate that E and RM are viable alternatives as solid biofuels through synergistic mixtures and granulometric control, favoring the revaluation of agricultural waste and naturally growing species in the region for energy purposes.
Keywords: corn stover; espartillo; physicochemical characterization; solid biofuels; combustibility